APPLICATION OF MOLECULAR GENETICS TO IMPROVING THE QUALITY OF BEEF - Kirinus, Jackeline Karsten; Fruet, Ana Paula Burin; Teixeira, César; Dörr, Andrea Cristina; Nörnberg, José Laerte (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2014)
The beef cattle industry is of great economic importance in global and national context. The objectives of this paper is to review some important aspects of the application of molecular genetics to improving the quality of beef with a view to defining quality of meat product and more demanding consumer markets. Considering the need of the consumer market to assess the meat produced, it is necessary to know the economic characteristics of the product to be consumed, as well as standardize and implement more sophisticated techniques for the evaluation of the rheological properties of meat. In this context, due to the numerous biochemical processes which are involved in the activation systems of proteolytic enzymes and degradation of myofibrillar proteins, molecular methods are being used as a tool for rating the genetic factors that influence the tenderness of beef.